KEPEMIMPINAN GEREJA YANG KOLABORATIF DAN ADAPTIF DALAM MENGATASI KESENJANGAN ANTARA GENERASI TUA DAN GENERASI MUDA DI ERA DIGITAL - Heintje Barry Kobstan (Jurnal Penggerak, 2023)
Thegapbetweentheolderandyoungergenerationsneedstobeminimized.George and Nicolas in theirjournalexaminethegenerationalgapinchurchleadershipthatresultsinconflictanddivision.Thereasonisthatthereisawrongconcept in leadership in the church, the young are not consideredsotheyarenotgiventheopportunitytotake part in thechurchespeciallyindevelopingleadership.Tosupport this research with conceptualideasabout the leadership gap between the oldergeneration and theyounger generation with a generationgapapproachsoastoproducecollaborativeandadaptiveleadership,thisarticleiswrittenqualitativelywithadescriptivemethod.In the endtheauthormakesconclusionsbasedonthedescription, analysis,reflectionandofferofsolutionsthathavebeendone.Understanding the bridgesystemor generation gapbetween the leadershipoftheoldergeneration and the youngergenerationwillcreateaCollaborativeandAdaptiveLeadershipstyleinthedigitalera.Acollaborativechurchleadershipstylethatinvolvesolder and youngergenerationsindecision-makingprocessescreatesopportunitiestostrengthenintergenerationalrelationships, listentodiverseviews,andreachbetterdecisions.Generationgap is aconditioncausedbydifferencesinexperience,differences in attitudesbetweendifferentgenerationseventuallyleadtogapsor "distance"Theyoungergenerationismorefamiliarwithtechnologyand the digitalworldthantheoldergeneration.Thisresearchframeworkisnotonlylimited to discussingthegapbetweengenerations, buthowtodevelopcollaborativeandadaptiveleadershipconcepts.